A switchable dual organocatalytic system and the enantioselective total synthesis of the quadrane sesquiterpene suberosanone. Issue 39 (25th April 2016) - Ren, Yajun; Presset, Marc; Godemert, Jeremy; Vanthuyne, Nicolas; Naubron, Jean-Valère; Giorgi, Michel; Rodriguez, Jean; Coquerel, Yoann
Abstract : Switch it! The combination of aminocatalysis and N-heterocyclic carbene catalysis has been extended to a switchable dual catalytic system. Abstract : The combination of aminocatalysis with N-heterocyclic carbene catalysis has been extended to a switchable dual catalytic system, which allowed a direct enantioselective entry to bridged bicyclo[3. n .1] ring systems and the total synthesis of the natural product (1 R )-suberosanone.